Persepsi Masyarakat Terhadap Pelaku Kekerasan dalam Rumah Tangga (Studi Kasus di Mapili Barat Polewali Mandar - Helmalia Darwis; Inayah Rohmaniyah (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2022)
This paper explores the public perception of perpetrators of domestic violence in West Mapilli. This study aims to determine the forms of domestic violence in West Mapilli, what factors influence the occurrence of domestic violence, then what are the implications of the perpetrators on domestic violence in West Mapilli. The type of research conducted is qualitative by using a sociological approach and selecting several informants to conduct interviews, observations and documentation. The results of this study indicate that the perpetrators of domestic violence include emotional violence, intimidation or threats and physical violence. Then the causes of domestic violence can be classified into two factors, namely internal and external factors. For the perpetrators of domestic violence, please be informed about the acts of harboring violence against loved ones that they have committed. That the violence he committed was deviating from religious values, because every religious person is not allowed to hurt one another. Keywords: Public Perception, Domestic Violence Perpetrator, Polewali Mandar